When bad grammar happens to good people : how to avoid common errors in English - Batko, Ann (Career Press, 2004)
Contains a comprehensive reference guide designed to identify and correct the most common errors in written and spoken English including pronoun use, verb tenses, modifiers, and mispronounced words.